ENERGY TRANSFER FROM THE PV PANEL TO BATTERY VIA BUCK-BOOST CONVERTER - Dagal, Idris; Akin, Burak (MATTER: International Journal of Science and Technology, 2019)
This paper deals with the means of transferring energy from the input to the output. The buck boost converter is considered as a maximum power point tracker or power equilibrium device used between the photovoltaic solar system and the battery by supplying the desired power for the stand-alone system requirements. The system energy is assigned by SLP190S-24 High Efficiency Monocrystalline PV module based Perturb and Observe (P&O) MPPT algorithm with a selected lead acid battery bank of 24 Volts. In order to achieve this energy transfer with minor energy losses, Buck-Boost converter with the switching frequency of 25Khz is designed for charging the lead acid battery applied in standalone system. The MATLAB SIMULINK is used to validate the accuracy and effectiveness of the designed Buck-Boost converter simulation results. The result clings to the value of 99.72% for the combined Tracking and conversion efficiencies.